Perbandingan Jumlah Leukosit Menggunakan Ekstrak Buah Limau Kuit sebagai Reagensia Alternatif - Muhammad Arsyad; Nurul Amalia; Nurbidayah Nurbidayah (Jurnal Sehat Mandiri, 2025)
Limau kuit (Citrus hystrix DC) is a fruit that has a distinctive sour taste. The sourness in limau kuit extract can be used to replace glacial acetic acid, which is one of the compounds found in reagents used to aid in the diagnosis of certain diseases. One of the reagents that contains acetic acid is Turk’s solution, which functions to stain leukocyte cells and lyse other cells except leukocytes, thus enabling leukocyte count analysis. The objective of this study was to count leukocytes using a modified Turk’s solution made from limau kuit extract and compare the results with those obtained using commercial Turk’s solution. The study design was a randomized post-test only controlled group design, using instruments such as a microscope, micropipette, test tubes, and an improved Neubauer chamber. The research was conducted in the pathology laboratory of Universitas Borneo Lestari in October 2024. Leukocyte count examinations were performed in 16 repetitions, followed by statistical data analysis using the Independent Sample T-Test. The results showed that the leukocyte counts obtained using the modified Turk’s solution from limau kuit extract did not show a significant difference. The difference in mean leukocyte count was 40.63 cells/mm³, with a median difference of 100 cells/mm³, a maximum difference of 150 cells/mm³, and a minimum difference of 200 cells/mm³. Microscopically, erythrocytes were completely lysed and leukocytes were clearly visible; however, bacterial contamination was still observed in the field of view. In conclusion, the modification of Turk’s reagent using limau kuit extract showed no significant difference between the control group (commercial Turk’s reagent) and the treatment group.